2014
DOI: 10.1177/1049732314548880
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Adults With Epilepsy and Their Support Persons on Self-Management Support

Abstract: Social support is an important mechanism for improving self-management, although little is known about its role in epilepsy self-management. We examined the type of support provided to people with epilepsy and its influence on self-management. We conducted in-depth interviews with 22 people with epilepsy and 16 support persons, representing 14 pairs and 10 unpaired individuals. We analyzed the data using principles of grounded theory. Supporters, who were mainly parents and spouses, aided people with epilepsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 55 publications
1
13
0
3
Order By: Relevance
“…For this analysis, we developed a model based on participants’ experiences with living with epilepsy and how the experiences of PWE and PSP are intertwined. The methods for this study have been described elsewhere [29, 30] and are summarized below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this analysis, we developed a model based on participants’ experiences with living with epilepsy and how the experiences of PWE and PSP are intertwined. The methods for this study have been described elsewhere [29, 30] and are summarized below.…”
Section: Methodsmentioning
confidence: 99%
“…Support persons can play an important role in providing PWE with the resources and emotional support needed to deal with and manage epilepsy. For example, support persons give reminders to take medication, monitor medication taking, and support strategies for reducing exposure to triggers [2830]. The support provided through marriage appears to offset some of the social, functional, and economic challenges faced by PWE [8].…”
Section: Introductionmentioning
confidence: 99%
“…Not only do individuals living with epilepsy or PNES have to adjust to the unpredictability and distressing nature of seizure events, they also have to manage the sequelae associated with their seizures. For many, stigma, discrimination, the limitation of activities, and the challenges associated with treatment is a greater burden than seizure events themselves (Kerr, Nixon, & Angalakuditi, 2011;Rawlings & Reuber, 2016;Walker et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Social resources and the interventions by others to meet needs are the social determinants in an individual's life, or the social support system available to help or intervene either with physical participation or through encouragement and psychological intervention. A study by Dilioro, Hennessy, and Manteuffel found that the individual's social support is important for medication adherence in individuals with epilepsy, while Walker et al . also studied the influence of a support system on individual self‐management in epilepsy and found that social support was an integral part of success.…”
Section: Construct Of Functional Mastery Of Health Ownershipmentioning
confidence: 99%